Development and Characterization of Polyherbal Hair Oil for Prevention of Hair Fall (Asian Journal of Pharmaceutics (AJP), 2023)
Herbs are an essential component of the health-care system in Ayurvedic medicine. In addition to being used inmedicine, herbs are also used to make a variety of cosmetics and colors, as well as to enhance physical beauty. Thepurpose of the present study is to prepare herbal hair oil from the fresh leaves of different plants. Making herbal hairoil with fresh curry leaves, hibiscus flowers, and fenugreek seeds is the goal of the present study. According to theAyurvedic pharmacopeia, the oil was manufactured. Different formulations were made, and the best formulation,f2, produced superior results as the pH ranged between 6 and 4.7, whereas f4’s saponification value was discoveredto be 245.43 and f2’s acid value was 4.7. The prepared herbal hair oil was assessed using a number of criteria,including organoleptic qualities, pH, viscosity, acid value, and saponification value. On our forearm, we evaluatethe prepared compositions for primary skin irritation. The aforementioned criteria were found to be satisfactoryand within acceptable limits. Of the three concentrations of herbal hair oil created, the third concentration producedsuperior outcomes to the other two. All the values in the evaluation of the finished product showed that they werewithin acceptable limits. Hence, it is concluded that the oil is beneficial in maintaining good hair growth, turninggrey hairs black, providing protection from dandruff, and resulting in lustrous-looking hair.